+0  
 
0
546
2
avatar

if a=3x^2+5x-6 and B=-2x^2-6x+7 then waht does A+B=?

Guest Jun 9, 2015

Best Answer 

 #4
avatar+26720 
+5

Simply add together the terms with the same power of x (or subtract if needed):

 

A + B = 3x^2 + 5x - 6 -2x^2 - 6x + 7 → x^2 - x + 1

.

Alan  Jun 9, 2015
 #1
avatar+55 
0

You need numbers for the variables as I nor My source can solve your problem.

VlenkovAryguyta  Jun 9, 2015
 #4
avatar+26720 
+5
Best Answer

Simply add together the terms with the same power of x (or subtract if needed):

 

A + B = 3x^2 + 5x - 6 -2x^2 - 6x + 7 → x^2 - x + 1

.

Alan  Jun 9, 2015

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.